The Relationship Of Board Characteristics And Carbon Management Strategy Of Listed Companies In Malaysia - Chuah, Ren Hui (Universiti Malaysia Sarawak (UNIMAS), 2019)
There has been overwhelming scientific evidence that climate change presents serious risks to humanity, requiring an urgent global response to avoid its catastrophic impact. The main objective of the study was to investigate the relationship between board characteristics in term of board size, board gender, board independence, educational level of board members and nationality of board members, and carbon management strategy (CMS). CMS was measured by adopting the prior study of Yunus et al. (2016) which consists of 6 criteria. 288 samples of public listed firms in Bursa Malaysia for year 2016 had been examined. The data were collected from both annual reports and firm websites. After accounting for control variables such as firm age, firm size and leverage, the results showed the board gender had negative relationships with CMS. This suggested that women directors have no power in term of owning the directorship in a company. Moreover, the companies are electing less women as part of the directors which caused the negative relationship occurred. The results also showed that there was mixed relationship between control variables and CMS. For future research, this paper recommended to extend the study by using whole sample of public listed firms in Bursa Malaysia as other measurement in CMS.